Analyzing the Mediating Role of Job Satisfaction in the Garment Industry as a Determinant of Performance: Work-Life Balance - Maria Sri Meidarni Laia; Dyah Palupiningtyas (Badan Penerbit STIEPARI Press, 2024)
The goal of this study is to find out how job happiness and employee performance at the clothing firm PT Sumber Bintang Rezeki are impacted by maintaining a healthy work-life balance. This study employs quantitative techniques and is intended to function as an explanatory investigation. Three hundred employees were chosen, and their surveys were collected using a random ratio approach. Path analysis evaluates the connections between direct and indirect variables in data analysis. The findings indicate that worker happiness and employee performance are positively and significantly impacted by maintaining a balance between work and home life. Furthermore, there is a favorable and noteworthy correlation between work happiness and employee performance. Further findings indicate a substantial relationship between job happiness and employee performance as well as the balance between privacy and competence. Stated differently, preserving a healthy balance between work and home life not only directly affects performance but also contributes to job satisfaction, which raises performance levels overall. Guidance helps workers establish a balance between work and job pleasure, which is important for improving employee performance in the apparel business, according to this research.